Aspects of stereocontrol in the L-Selectride reduction of 4-acyl-1,3-dioxolane derivatives - Robertson, J; Unsworth, W; Lamont, S (2010)
The application of L-Selectride, either alone or in combination with ZnCl2, to aryl ketones 1, 8 and 11 resulted in highly anti-stereoselective reduction. In contrast, lactols 22 and 23 gave a moderate syn-preference using L-Selectride alone and a high syn-preference in the presence of ZnCl2. Uniquely, high anti- stereoselectivity was observed in the reduction of o-anisyl lactol 37 with L-Selectride alone, which was switched to a high syn-preference when ZnCl2 was present. © 2010 Elsevier Ltd. All rights reserved.